2023
DOI: 10.30892/gtg.50426-1144
|View full text |Cite
|
Sign up to set email alerts
|

The Attraction of Can Tho City, Vietnam as a Tourist Destination

Luu Thanh Duc HAI,
Quoc Nghi NGUYEN,
Khuu Ngoc HUYEN

Abstract: This study aims to demonstrate the influencing factors on the destination attractiveness of Can Tho City, Vietnam. From October 2022 to November 2022, the study collected data using a convenient sampling method, with a sample size of 268 tourists. A mixed-method research approach combining qualitative and quantitative research methods was employed to validate the research hypotheses. For qualitative research, a focus group discussion method was conducted to identify appropriate scales for the research model. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
1
1
0
Order By: Relevance
“…Therefore, investment in infrastructure, facilities, and equipment by ecotourism destinations will improve service quality and enhance the satisfaction of international tourists. Indeed, tangible factors contribute positively to the quality service experience of tourists (Hai et al, 2023). The finding is consistent with studies proposed by Ibrahim et al (2015), Shah et al (2018), Long (2019), Masrurul (2019), Thuy (2020), Hong et al (2022), Cheraghzadeh et al (2023, Sapkota et al (2023), andSugiama et al (2024).…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, investment in infrastructure, facilities, and equipment by ecotourism destinations will improve service quality and enhance the satisfaction of international tourists. Indeed, tangible factors contribute positively to the quality service experience of tourists (Hai et al, 2023). The finding is consistent with studies proposed by Ibrahim et al (2015), Shah et al (2018), Long (2019), Masrurul (2019), Thuy (2020), Hong et al (2022), Cheraghzadeh et al (2023, Sapkota et al (2023), andSugiama et al (2024).…”
Section: Discussionsupporting
confidence: 89%
“…In the context of water parks, perceived value, and water park image have a direct effect on customer satisfaction, which then leads to a positive influence on revisit intention (Ghorbanzade et al, 2019). The tourism destination depends on recreational activities and infrastructure factors (Hai et al, 2023). Other studies confirmed that recreational attraction has a significant impact on revisit intention (Mahdzar et al, 2015;Markus et al, 2019).…”
Section: The Relationship Between Water Park Components and Satisfact...mentioning
confidence: 96%